The relationship between parental feeding styles and the nutritional status of toddlers among working mothers in Yogyakarta - Riska Amelia; Ceria Ciptanurani; Silvi Lailaltul Mahfida (Universitas Ahmad Dahlan, 2024)
The increasing number of mothers working outside the home represents a significant social and economic change. The rise in women's workforce participation has notably impacted family dynamics, particularly influencing working mothers' feeding styles on child development and nutritional status. This study aims to determine the relationship between parental feeding style and toddler's nutritional status among working mothers. This is an observational analytic study with a cross-sectional design. The target population includes all working mothers with toddlers in the Yogyakarta Special Region. Samples were purposively selected, comprising 211 mother-toddler pairs. Data were collected through self-administered online and offline questionnaires on respondent characteristics and feeding styles using the Caregiver Feeding Style Questionnaire. Toddler nutritional status data were measured using weight-for-age (W/A), height-for-age (H/A), and weight-for-height (W/H) indices, obtained through direct measurements of weight and height. The Spearman rank correlation test was used to evaluate the relationship between feeding style and children's nutritional status. There was a significant negative correlation between the responsive aspect of parenting feeding style and the nutritional status on the H/A index, rₛ(210) =-0.17, p=.014. However, no significant correlations were found between the demanding aspect of feeding style and the nutritional status on the W/A, H/A, and W/H indices (rₛ(210)=-0.03, p=.662; rₛ(210)=-0.07, p=.322; rₛ(210)=-0.08, p=.226, respectively). Similarly, the responsive aspect of parenting style was not significantly correlated with the nutritional status on the W/A and W/H indices (rₛ(210)=0.01, p=.947; rₛ(210)=-0.11, p=.115, respectively). In conclusion, a relationship was found between responsive parenting feeding style and nutritional status on the H/A index. However, no significant relationships were observed between demanding feeding style and nutritional status on the W/A, H/A, and W/H indices, or between responsive style and the W/A and W/H indices. Public health interventions should focus on promoting responsive feeding styles among working mothers to improve child nutritional outcomes.